Low SARS-CoV-2 viral load among vaccinated individuals infected with Delta B.1.617.2 and Omicron BA.1.1.529 but not with Omicron BA.1.1 and BA.2 variants - T. Selvavinayagam, Sivaprakasam; Kong Yong, Yean; Joseph, Narcisse; Hemashree, Kannan; Yien Tan, Hong; Zhang, Ying (Frontiers, 2022)
The rapid spread of SARS-CoV-2 variants in the global population is indicative of the development of selective advantages in emerging virus strains. Here, we performed a case-control investigation of the clinical and demographic characteristics, clinical history, and virological markers to predict disease progression in hospitalized adults for COVID-19 between December 2021 and January 2022 in Chennai, India. COVID-19 diagnosis was made by a commercial TaqPath COVID-19 RT-PCR, and WGS was performed with the Ion Torrent Next Generation Sequencing System. High-quality (<5% of N) complete sequences of 73 Omicron B.1.1.529 variants were randomly selected for phylogenetic analysis. SARS-CoV-2 viral load, number of comorbidities, and severe disease presentation were independently associated with a shorter time-to-death. Strikingly, this was observed among individuals infected with Omicron BA.2 but not among those with the BA.1.1.529, BA.1.1, or the Delta B.1.617.2 variants. Phylogenetic analysis revealed severe cases predominantly clustering under the BA.2 lineage. Sequence analyses showed 30 mutation sites in BA.1.1.529 and 33 in BA.1.1. The mutations unique to BA.2 were T19I, L24S, P25del, P26del, A27S, V213G, T376A, D405N and R408S. Low SARS-CoV-2 viral load among vaccinated individuals infected with Delta B.1.617.2 and the Omicron BA.1.1.529 variant but not with Omicron BA.1.1 or BA.2 suggests that the newer strains are largely immune escape variants. The number of vaccine doses received was independently associated with increased odds of developing asymptomatic disease or recovery. We propose that the novel mutations reported herein could likely bear a significant impact on the clinical characteristics, disease progression, and epidemiological aspects of COVID-19. Surging rates of mutations and the emergence of eclectic variants of SARS-CoV-2 appear to impact disease dynamics.